MUTU FISIK BUAH TIMUN APEL (CUCUMIS SP.) DENGAN PEMUPUKAN PUPUK TUNGGAL N, P DAN K YANG BERBEDA DI TANAH KAHAT UNSUR HARA - Johannes Rongga Pamungkas Sitorus; Fawzy Muhammad Bayfurqon; Slamet Abadi (Universitas Lambung Mangkurat, 2021)
This research was conducted at the Ulekan Street HS Screen House. Ronggo Waluyo, Puseurjaya Village, Teluk Jambe Timur District, Karawang Regency, West Java. The experiment was conducted from July-August 2020. The research method used was experimental, with 3 replications of a completely randomized design (CRD). This study aims to determine the physical quality of apple cucumber by giving N, P and K fertilizers in nutrient-deficient soils. The research was conducted using a completely randomized design method (CRD) with 1 factor (Urea: 250 kg / ha, SP-36: 450 kg / ha and KCL: 250 kg / ha) with 8 levels and 3 replications, consisting of (K0) without Fertilizer N, P and K, (K1) Fertilizer N, P and K, (K2) Urea, (K3) KCL, (K4) SP-36, (K5) Fertilizer Urea and KCL, (K6) Fertilizer SP 36 and KCL and (K7) Urea and SP-36 fertilizers. The results showed that the best treatment was found in N, P and K (K1) with fruit weight yielding 260, 67 gr, fruit diameter 75.43 mm thick fruit flesh 14.14 cm, edible portion 68.59 kf and sweetness content. fruit 13.33%